First-principle investigations of structural, electronic, magnetic and optical properties of bulk BiVO3. Issue 95 (28th September 2016) - Liu, Biao; Wu, Li-Juan; Zhao, Yu-Qing; Wang, Lin-Zhi; Cai, Meng-Qiu
Abstract : The structural, electronic, magnetic and optical properties of bulk BiVO3 are investigated by first-principle calculations. Abstract : The structural, electronic, magnetic and optical properties of bulk BiVO3 are investigated by first-principle calculations. The calculated results show that the ground state of BiVO3 perovskites is Pnma with C-type antiferromagnetic ordering (C-AFM) with a band gap of 1.79 eV. The hybridization between Bi–O and V–O with interplay play important roles for the nature of the ferromagnetism. Furthermore, our study shows that it has strong light absorption, but low reflection efficiency between 400 nm and 760 nm in the visible light region. It indicates that BiVO3 will be a promising photocatalyst with favorable photocatalytic activity in the visible region. Our results will provide theoretical guidance for BiVO3 synthesis and application.